Model Penilaian Berbasis Portofolio dalam Pengembangan Ranah Afektif Santri di Pesantren Hubulo Kabupaten Bone Bolango Provinsi Gorontalo - Ahmad Fauzi; Said Subhan Posangi; Asna Usman Dilo (UIN Fatmawati Sukarno Bengkulu, 2022)
The portfolio-based assessment model is an approach in assessing students’ performance. And the development students’ affective domain is the process of collecting data and information by using instrument about attitudes, values, personality, and students’ morals both in learning and outside learning. The objective of this research is to identify and analyze The portfolio-based assessment model in developing students’ affective domain, as well as to be a reference for the next research. The method used in this research was a qualitative method with a naturalistic and psychological approach. The results of this research indicated that the The portfolio-based assessment model has its own assessment adventages from other assessments, but in general The portfolio-based assessment applied at the Hubulo Islamic Boarding Schoolnhas not been able to improve the development of student’ affective domain. This happens because The portfolio-based assessment model at the Hubulo Islamic Boarding School was very rigid and inflexible, while the time for developing students’ affective domain was very low so that the goals of developing students’ affective domain were not maximally achieved. The difference between this research and the previous one was the research location and the object under studied.